Relações de gênero na carreira acadêmica em Engenharia Civil - Pinto, Érica Jaqueline Soares (2019)
This research, which is part of a program funded by the National Council for Scientific and Technological Development (CNPq), aimed to analyze how gender relationships may condition teaching in higher education career of women who work at the Civil Engineering course of a northeast Federal Institution, in Brazil. The theoretical background that supports this study is in the confluence of gender studies, science and technology and academic career. This is a qualitative research that encompasses 10 female and 3 male professors. It was developed in four steps. The first was a survey that considered women admission at the department, throughout its existence, and its current constitution considering sex, by collecting this data through the Integrated System of Academic Activities Management (SIGAA) and at the department itself. The second was a research and analysis of CNPq’s Lattes curriculum of all active professors: 10 women and 32 men. The third compared the curriculum of 3 female and 3 male professors with an equivalent admission at the career, to understand if there are any possible inequalities between sexes in what refers to “scientific power” and “academic power”, Pierre Bourdieu’s categories. The fourth and last step was constituted by interviews carried out with 3 male professors and the 10 female professors of the department, to verify the gender constraints in their teaching and scientific paths. It was possible to notice that although the department have integrated more women during the last few years, specially from 2008 on, the thesis that the teaching career of the female professors of Civil Engineering course at this Federal Institution is hampered due to the gender socialization is confirmed. That turns inequalities into something natural, through sexual differences, perpetuating the sexual division of labor.Furthermore, the androcentric culture of science and academia is realized through tangible and or subtle boundaries to the valorization and progress of women, what is even more severe at Civil Engineering, dominated by men. The comparative analysis showed that men tend to ascend more, specially at the “scientific power” and, when they do not stand out, they do not worry about demands regarding their low productivity, what does not happen with women. They face, mainly, the challenges of constantly having to prove competence, going through reproduction and the break of masculine stereotypes, besides conciliating career and motherhood. Some understand it as gender challenges, others do not see it like that, however, in general, they express pleasure for what they do and are self-confident, determined and are not intimidated by these circumstances, what points to a standards’ breaking of what is socially expected from women. Some, in spite of reproducing some masculine stereotypes, question the course’s strict practices and value more humanistic aspects. It is possible to conclude that the growing participation of women in Civil Engineering may contribute to modify the patriarchal and androcentric structure of this field.